(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
The term «neuromarketing» and analysis of its essence as a new direction of development of the marketing environment are considered in the article. Characteristics of basic tools and methods using in sensory marketing are given and trends of using it in practical terms are identified in the work.